2021
DOI: 10.3390/d13100488
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Three Novel Cytospora Species in Thailand and Their Antagonistic Potential

Abstract: During an ongoing research survey of saprobic fungi in Thailand, four coelomycetous strains were isolated from decaying leaves in Chiang Mai and Phitsanulok Provinces. Morphological characteristics demonstrated that these taxa are typical of Cytospora in forming multi-loculate, entostromatic conidiomata, branched or unbranched conidiophores, with enteroblastic, phialidic conidiogenous cells and hyaline, allantoid, aseptate conidia. Multiloci phylogeny of ITS, LSU, ACT, RPB2, TEF1-α and TUB2 confirmed these tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Wood-rotting fungi are an extensively studied group of Basidiomycota [17,[32][33][34], but Chinese wood-rotting fungal diversity is still not well known, especially in the subtropics and tropics. Many recently described taxa of fungi are from subtropical and tropical areas [17,[35][36][37][38]. The new species presented in the current study is also from the subtropics.…”
Section: Discussionmentioning
confidence: 66%
“…Wood-rotting fungi are an extensively studied group of Basidiomycota [17,[32][33][34], but Chinese wood-rotting fungal diversity is still not well known, especially in the subtropics and tropics. Many recently described taxa of fungi are from subtropical and tropical areas [17,[35][36][37][38]. The new species presented in the current study is also from the subtropics.…”
Section: Discussionmentioning
confidence: 66%
“…For example, Botrel et al [ 83 ] reported that saprobic Phialomyces macrosporus has the potential to be employed in the management of coffee halo blight, which caused by Pseudomonas syringae pv. garcae , Monkai et al [ 84 ] isolated four Cytospora species from decaying leaves, and three of them ( Cytospora shoreae , C. phitsanulokensis and C. chiangmaiensis ) showed 60–75% growth inhibition against pathogens Colletotrichum viniferum and Fusarium sambucinum in vitro. Therefore, deep studies of saprobic fungi are necessary, especially secondary metabolites of saprobic fungi and their life mode changes.…”
Section: Discussionmentioning
confidence: 99%
“… Cytospora is distributed worldwide and often known to be associated with plant diseases ( Monkai et al 2021 ; Pan et al 2021 ; Lin et al 2022 ; Travadon et al 2022 ). For example, C. chrysosperma is the main canker disease pathogen of polar and willow trees in China ( Fan et al 2014 ; Wang et al 2015 ; Lin et al 2023 ); C. kuanchengensis and additional five species are associated with Chinese chestnut cankers ( Jiang et al 2020 ); Fifteen Cytospora species were identified from destructive canker and dieback pathogens of woody hosts in the USA ( Lawrence et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%